IMPACT OF CLIMATE CHANGE ON THE GROWTH, YIELD, AND SUNFLOWER CULTIVAR PERFORMANCE UNDER THE INFLUENCE OF PLANT DENSITY. - Sinan A. Abas; Zeyad A. Abdulhamed; Nihad M. Abood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
To determine the impact of climate change on the growth and yield of sunflower when planted at two different climatic times, a field experiment was conducted in Anbar Governorate, specifically in the Ramadi district, in the fields of one of the farmers. Five cultivars were used: "Aqmar", "Haysen", "Isaqi", " Flami a and "Tarzan", at three plant densities of 88,900, 66,670, and 53,300 plants ha-1. A randomized complete block design (R.C.B.D) was used with three replications, in a split plot arrangement, where plant densities occupied the main plots and cultivars occupied the sub plots. The results indicated the superiority of the cultivar "Flami" with the shortest flowering duration at 66.78 and 62.51 days for the spring and autumn seasons, respectively. Additionally, the selected cultivar "Haysen" exhibited superior leaf area 5690 and 5300 cm² for the spring and autumn seasons, respectively. Furthermore, the cultivar "Tarzan" surpassed others by providing the highest disc area at 355.0 and 327.4 cm² for the spring and autumn seasons, respectively. Moreover, the same cultivar outperformed in terms of seed number per disc and seed yield, with 1186 and 1164 seeds, and 5.665 and 5.409 grams disc-1 for the spring and autumn seasons, respectively. The high plant density exhibited superiority in seed yield, providing the highest yield of 6.100 and 5.936 µg ha-1 for the spring and autumn seasons, respectively, compared to the low plant density of 4.571 and 4.338 µg ha-1 for the spring and autumn seasons, respectively. Regarding the interaction between cultivars and plant density, the cultivar "Tarzan" outperformed with the highest yield of 6.528 and 6.385 µg ha-1 for the spring and autumn seasons, respectively, with an increase of 50.17% and 55.66% compared to the cultivar "Isaqi" for the spring and autumn seasons, respectively, at a plant density of 55,30 plants ha-1.